ECOPHUSION: Pemanfaatan Kulit Pisang Cavendish (Musa acuminata) sebagai Label Biofilm Smart Packaging Berbasis Biosensor pH dari Kulit Buah Naga (Hylocereus polyrhizus) - Maourin Ferdina Kusnul Kasanah; Fariha Rahma Mardhiyah; Indrato Dwi Atmoko; Susanti Rahayu (Jurnal Integrasi Sains dan Quran, 2025)
Food waste is one of the largest contributors to waste in Indonesia, accounting for 39.77% of total waste. The decomposition process of food waste produces carbon gas emissions that are harmful to the environment. The main cause of this problem is the lack of consumer knowledge about product packaging and the mismatch of packaging with product quality. This alternative solution is to use pH sensor-based smart packaging label by utilizing banana peel and dragon fruit peel anthocyanins. Banana peels are rich in cellulose, lignin, pectin, and protein, which provide structural strength to the biofilm. Meanwhile, dragon fruit peels contain anthocyanin, a natural pigment that provides color and is able to detect changes in pH and oxidation, making it effective as a biosensor for meat deterioration. Anthocyanins, flavonoids and phenolic acids, allow detection of chemical changes in meat that begin to deteriorate with a clear color change. The purpose of this study is to determine how to make biofilm smart packaging based on pH biosensors from dragon fruit peels and banana peels to monitor and detect the quality of food products and reduce methane gas emissions due to food waste and plastic packaging waste. This type of research is descriptive qualitative which focuses on product manufacturing and product testing. Data collection was done by observation and literature study. Indicators of product effectiveness meet: biofilm sensitivity test to pH, indicator film label application test on meat and meat weight loss test. The results of the biofilm sensitivity test to pH showed that an increase in pH value was directly proportional to the change in color of the biofilm to be more brown. In addition, the indicator label application test on chicken meat also showed that the color change of the label followed the increase in pH in chicken meat, which over time had an effect on increasing the weight loss of chicken meat.